Responses to iron oxide and zinc oxide nanoparticles in echinoderm embryos and microalgae: uptake, growth, morphology, and transcriptomic analysis. Issue 10 (25th November 2020) - Genevière, Anne-Marie; Derelle, Evelyne; Escande, Marie-Line; Grimsley, Nigel; Klopp, Christophe; Ménager, Christine; Michel, Aude; Moreau, Hervé
Abstract: We investigated the toxicity of Iron oxide and Zinc oxide engineered nanoparticles (ENPs) on Paracentrotus lividus sea urchin embryos and three species of microalgae. Morphological responses, internalization, and potential impacts of Fe2 O3 and ZnO ENPs on physiology and metabolism were assessed. Both types of ENPs affected P. lividus larval development, but ZnO ENPs had a much stronger effect. While growth of the alga Micromonas commoda was severely impaired by both ENPs, Ostreococcus tauri or Nannochloris sp. were unaffected. Transmission electron microscopy showed the internalization of ENPs in sea urchin embryonic cells while only nanoparticle interaction with external membranes was evidenced in microalgae, suggesting that marine organisms react in diverse ways to ENPs. Transcriptome-wide analysis in P. lividus and M. commoda showed that many different physiological pathways were affected, some of which were common to both species, giving insights about the mechanisms underpinning toxic responses.